Chaetocin induced chromatin condensation: effect on DNA repair signaling and survival. (3rd April 2021) - Sak, A.; Bannik, K.; Groneberg, M.; Stuschke, M.
Abstract: Purpose: The aim of the present study was to evaluate the effect of the histone lysine-methyltransferase (HKMT) inhibitor chaetocin on chromatin structure and its effect on ionizing radiation (IR) induced DNA damage response. Methods: Concentration and time-dependent effects of chaetocin on chromatin clustering and its reversibility were analyzed by immunofluorescent assays in the non-small cell lung carcinoma (NSCLC) cell lines H460 and H1299Q4 and in human skin fibroblasts. In addition, IR induced damage response (γH2AX, 53BP1, and pATM foci formation) was studied by immunofluorescent assays. The effect on survival was determined by performing single-cell clonogenic assays. Results: Chaetocin significantly increased the radiation sensitivity of H460 (F test on nonlinear regression, p < .0011) and of H1299 ( p = .0201). In addition, treatment with 15 nM chaetocin also decreased the total radiation doses that control 50% of the plaque monolayers (TCD50) from 17.2 ± 0.3 Gy to 7.3 ± 0.4 Gy ( p < .0001) in H1299 cells and from 11.6 ± 0.1 Gy to 6.5 ± 0.3 Gy ( p < .0001). Phenotypically, chaetocin led to a time and concentration-dependent clustering of the chromatin in H1299 as well as in fibroblasts, but not in H460 cells. This phenotype of chaetocin induced chromatin clustering (CICC) was reversible and depended on the expression of the HKMTs SUV39H1 and G9a. Treatment with siRNA for SUV39h1 and G9a significantly reduced the CICC phenotype. Immunofluorescent assay results showed that the CICC phenotype was enriched for the heterochromatic marker proteins H3K9me3 and HP1α. γH2AX foci formation was not affected, neither in cells with normal nor with CICC phenotype. In contrast, repair signaling with 53BP1 and pATM foci formation was significantly reduced in the CICC phenotype. Conclusions: Treatment with chaetocin increased the radiation sensitivity of cells in vitro and DNA damage response, especially of 53BP1 and ATM-dependent repair by affecting chromatin structure. The obtained results support the potential use of natural HKMT inhibitors such as chaetocin or other bioactive compounds in improving radiosensitivity of cancer cells.